Staged Surgical Palliation for HLHS in a Girl with Severe Factor X Deficiency - Elmahrouk, Ahmed F.; Ismail, Mohamed F.; Bugis, Abdulbadee; Badawy, Nashwa; Aboelghar, Hesham Mohamed; Hamouda, Tamer; Jamjoom, Ahmed (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Background Factor X deficiency (also known as Stuart–Prower factor deficiency) is an autosomal recessive extremely rare hereditary hematologic disorder, affecting around 1:1,000,000 of the general population.Case Presentation This case report describes a patient with hypoplastic left heart syndrome and severe factor X deficiency, who underwent staged surgical palliation. From stage 1 Norwood palliation, through superior cavopulmonary anastomosis and ending with total cavopulmonary connection with satisfactory hemostasis and no significant perioperative bleeding complication.Conclusion The need to maintain hemostasis while aiming to prevent intracardiac thrombosis requires multidisciplinary team approach including hematologist, cardiac surgeon, pediatric cardiac intensivist, and anesthesiologist along with meticulous hemostasis during surgery and careful monitoring of coagulation profile in the postoperative period.
Keywords: factor X deficiency; hypoplastic left heart syndrome; Norwood procedure; superior cavopulmonary anastomosis; total cavopulmonary connection